La distribución de las facultades impositivas en el sistema federal mexicano de acuerdo con la constitución política de los estados unidos mexicanos y el sistema nacional de coordinación fiscal. - Zazueta Gutiérrez Carreras, Gabriel Franco (My University, 2021)
This research work proposes to take a look at the federalism contravention in the magna carta on behalf of the Supreme Court of Justice of the Nation; this, based on the extensive interpretation that, in this regard, it makes in favor of the federation of article 73, section VII, in relation to article 124, both of the Political Constitution of the United Mexican States. Also, the insufficiency of fiscal resources available to the federal entities to defray their public expenditure based on said interpretation and its consequent creation of the National System of Fiscal Coordination, which aims to resolve the issue of tax competition, is observed. On the other hand, legal solutions and benefits for an adequate interpretation in relation to fiscal federalism in Mexico and, therefore, a different distribution of taxation powers between the different levels of Government are proposed. In this order of ideas, this analysis is carried out in the light of the Political Constitution of the United Mexican States of 1917 and the Fiscal Coordination Law in force, with the purpose of stablishing a new criterion of interpretation, in which the form of Government of the country and the sovereignty of the federative entities are respected.
Capítulo 2. Antecedentes, teoría, conceptos, formas de Estado y de Gobierno en México -- Capítulo 3. El sistema impositivo en México y el caso España -- Capítulo 4. Metodología para probar la hipótesis y escuela de interpretación
Keywords: fiscal decentralization; financing systems; federal entities; taxation powers; federal republic; subnational goverments; Derecho - Tesis